2019
DOI: 10.1128/jvi.01324-19
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Fate of Endogenous Retrovirus Segregation in Wild and Domestic Cats

Abstract: Endogenous retroviruses (ERVs) of domestic cats (ERV-DCs) are one of the youngest feline ERV groups in domestic cats (Felis silvestris catus); some members are replication competent (ERV-DC10, ERV-DC18, and ERV-DC14), produce the antiretroviral soluble factor Refrex-1 (ERV-DC7 and ERV-DC16), or can generate recombinant feline leukemia virus (FeLV). Here, we investigated ERV-DC in European wildcats (Felis silvestris silvestris) and detected four loci: ERV-DC6, ERV-DC7, ERV-DC14, and ERV-DC16. ERV-DC14 was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 66 publications
1
20
0
4
Order By: Relevance
“…Among all species, chicken, mice, and cats are best analyzed concerning the endogenous retroviruses in their genomes. For example, during cat evolution various exogenous retroviruses infected different cat lineages and generated numerous endogenous retroviruses in the host genome, some of which remain replication competent [32]. These viruses also can recombine and integrate de novo.…”
Section: Discussionmentioning
confidence: 99%
“…Among all species, chicken, mice, and cats are best analyzed concerning the endogenous retroviruses in their genomes. For example, during cat evolution various exogenous retroviruses infected different cat lineages and generated numerous endogenous retroviruses in the host genome, some of which remain replication competent [32]. These viruses also can recombine and integrate de novo.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies revealed an intronic Alu insertion polymorphism in CD58 gene associated with multiple sclerosis risk possibly due to altering its mRNA splicing [ 30 , 31 ]. In domestic animals, RIPs also have been used for evolution and population genetic analysis in sheep [ 32 ], cat [ 33 ], chicken [ 34 ], and rabbit [ 35 ]. Several RIPs have been associated with phenotypic variation in farm animals, such as an ERV insertion in the 5’ flanking region of SLCO1B3 causing blue eggshell by promoting the expression of the SLCO1B3 gene in the uterus (shell gland) of the oviduct in chicken [ 36 , 37 ], the henny feathering allele harboring an insertion of an intact avian ERV at the 5'end of CYP19A1 [ 38 ], and the SINE insertions in the follicle stimulating hormone beta ( FSHβ) and the protein disulfide isomerase associated 4 ( PDIA4 ) genes associated with litter size variations in pigs [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was a very limited RT activity in the lynx samples when compared to the result of the latent infected domestic cat. Low activity could also be ascribed to an unrevealed endogenous retrovirus (ERV) ( 87 , 88 ). Furthermore, emergence of three FIV-seropositive lynx by WB in the same area (Jura North) nearly at the same time (2016–2017) can hardly be coincidental.…”
Section: Discussionmentioning
confidence: 99%